Poorer Long-Term Survival Associated with Monomorphic Post-Transplant Lymphoproliferative Disorder After Solid Organ Transplantation in Children. (July 2018) - Chiou, Fang Kuan; Sharif, Khalid; Perera, Thamara; Muiesan, Paolo; Vickers, Mark; Beath, Sue; Morland, Bruce; Mirza, Darius; Gupte, Girish
Abstract : Introduction: Post-transplant lymphoproliferative disorder (PTLD) is a major complication in paediatric solid organ transplantation (SOT) with poor survival rates reported at 50-80%. Less aggressive subtypes, such as early lesions and polymorphic PTLD, may respond to reduction of immunosuppression (RIS) alone. In contrast, monomorphic PTLD tends to be more advanced at presentation requiring further therapy such as rituximab (RTX), cytotoxic T-lymphocytes (CTL) and/or chemotherapy. This study aims to review a single-centre experience focusing on the treatment outcome and long-term prognosis of monomorphic PTLD (M-PTLD) in comparison with other PTLD (O-PTLD) subtypes. Materials and Methods: Paediatric SOT patients diagnosed with PTLD from 1989-2016 were retrospectively reviewed. PTLD was diagnosed on tissue biopsy and classified as early lesion, polymorphic, monomorphic or Hodgkin's subtypes based on established World Health Organisation histology criteria. Treatment protocol consisted of RIS as initial treatment. RTX was introduced to the treatment protocol since year 2000. CTL was available in 1999-2004 as part of a research trial, and since 2011 as approved treatment for PTLD. Results: Total of 37 patients were identified with median follow-up duration of 8 years (range: 1-25). Twenty-two had isolated liver (LTx), 1 had combined kidney and LTx, and 14 had intestinal transplantation with or without combined LTx. Median ages at transplant and PTLD diagnosis were 19 months (range: 6-129) and 35 months (range: 11-178) respectively. Median interval from transplant to PTLD was 6 months (range: 2–107). Most common histologic subtype was monomorphic (n=18), followed by early lesion (n=10), polymorphic (n=8) and Hodgkin's type (n=1). There was no difference in Epstein-Barr virus (EBV) serostatus at transplant or prior history of allograft rejection or sepsis between patients with M-PTLD versus O-PTLD. M-PTLD were more likely to present with multiple organ involvement compared to O-PTLD (67% vs 26%, p=0.014). Remission was achieved with RIS alone in 47% of patients with O-PTLD, as compared to 11% with M-PTLD (p=0.016). M-PTLD was associated with poorer overall remission rate at 6 months (67% vs 95%, p=0.029), and lower 2-year (59% vs 89%, p=0.042) and 5-year (47% vs 89%, p=0.009) survival rates compared to O-PTLD. At last follow-up, 44% of patients with M-PTLD were alive, as compared to 90% of other subtypes (p=0.003). While introduction of RTX did not appear to improve outcome, there is a significant trend towards improved survival rates in M-PTLD in association with the availability of CTL therapy. Better remission rates were achieved in CTL (86%) in M-PTLD as compared to RTX (44%). Figure. No caption available. Figure. No caption available. Conclusion: M-PTLD is associated with more advanced disease and significantly poorer prognosis in paediatric SOT patients in comparison to other histologic subtypes. CTL therapy, where available, may offer a better remission rate and improve overall survival in M-PTLD.